Cosmetology Advertising Perspectives: Applications of Ethical Theories during COVID-19 Crisis - Hemaloshinee, Vasudevan A.; Imran, Aslan (Sumy State University, Ukraine, 2021)
In a pandemic, there are no egalitarians because all citizens cannot treat equally, and a failure to consider ethical concerns before taking action led to a massive and preventable loss of life. As a result of the pandemic, there is a strong ethical or moral imperative to consider how to help the most generous people usage healthy products. Utilitarianism and Kantian have become popular ethical theories that state the right actions that layout clear and actionable principles. This paper reviews (1) how Utilitarianism and Kantianism theories could produce benefit arguments on ethical purchases of cosmetic products from an advertising context, (2) how these theories contributed in the context of COVID-19 to help reduce any harmful health issues via advertising, and (3) Utilitarianism and Kantian theories have proven useful during the COVID-19 pandemic, according to case studies of cosmetics products and advertising in Western and Asian contexts. In addition to these two ethical theories, this paper discussed other issues. The purpose is not to argue which theory is the only relevant ethical theory but to contend with pure utilitarianism. Kantian's finding was similar to the topic argument in other ways. However, both theories reviewed as the most effective way to help societies identify and perceive the necessary costs of goods values. Before adopting utilitarian or Kantian theories, the community must clearly understand these two theories' merit values in product advertising. In such a crisis, ethical theories practices should implement in all areas because ethical challenges would determine whether or not advertisers around the world adhered to ethical standards in devising new and innovative marketing strategies, practices, or tactics for the transition to this new norm.